2016
DOI: 10.1038/modpathol.2016.51
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a variant of t(14;18) negative nodal diffuse follicular lymphoma with CD23 expression, 1p36/TNFRSF14 abnormalities, and STAT6 mutations

Abstract: A predominantly diffuse growth pattern and CD23 co-expression are uncommon findings in nodal follicular lymphoma and can create diagnostic challenges. A single case series in 2009 (Katzenberger et al) proposed a unique morphologic variant of nodal follicular lymphoma, characterized by a predominantly diffuse architecture, lack of the t(14;18) IGH/BCL2 translocation, presence of 1p36 deletion, frequent inguinal lymph node involvement, CD23 co-expression, and low clinical stage. Other studies on CD23+ follicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 30 publications
7
51
2
Order By: Relevance
“…Our results are similar to those of Pham-Ledard et al and Streubel et al who observed, respectively, BCL2 breaks in 8.5% (seven of 47) and BCL6 breaks in 7% (two of 27) of cases in their series of PCFL. 22,28 We confirmed, as supposed previously, 12 that the del 1p36 described in a subset of NFL 11,19 is involved in the pathogenesis of this cutaneous lymphoma.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Our results are similar to those of Pham-Ledard et al and Streubel et al who observed, respectively, BCL2 breaks in 8.5% (seven of 47) and BCL6 breaks in 7% (two of 27) of cases in their series of PCFL. 22,28 We confirmed, as supposed previously, 12 that the del 1p36 described in a subset of NFL 11,19 is involved in the pathogenesis of this cutaneous lymphoma.…”
supporting
confidence: 90%
“…Interestingly, CFL frequently expressed CD23 (13 of 32, 40.6% cases of CFL versus one of 15, 6.7% cases of CMZL). This is not surprising, as CD23 expression is variable in NFL, observed preferentially in diffuse NFL or those harbouring the del 1p36, whereas CD23 is generally negative in mucosa‐associated lymphoid tissue (MALT) lymphoma and NMZL . In their series of PCFL, Goodlad et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…85 These latter 2 genetic alterations are also both occasionally seen in typical FL albeit at lower frequencies. 86 …”
Section: Follicular Lymphomamentioning
confidence: 99%